You Can't Get There From Here: An Urban Proposal - Wriston, Walter B. (Tufts Archival Research Center, 2007)
The document was created from the speech, "You Can't Get There From Here: An Urban Proposal," written by Walter B. Wriston for the New York Commerce and Industry Association on 25 October 1967. The original speech is located in MS134.001.001.00032.